The cost of firms' debt financing - Daniele Pianeselli; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
We provide an assessment of the determinants of the risk premia paid by non-financial corporations on long-term bonds. By looking at 5,500 issues over the period 2005-2012, we find that in recent years the sovereign debt market turbulence has been a major driver of corporate risk. Compared with the three-year period 2005-07 before the global financial crisis, in the years 2010-12 Italian, Spanish and Portuguese firms paid on average between 70 and 120 basis points of additional premium due to the negative spillovers from the sovereign debt crisis, while German firms got a discount of 40 basis points.
urn:nbn:de:hebis:30:3-324807
Keywords: G38; G32; 330; Corporate bonds; Risk-premium; Too big to fail; Sovereign debt crisis